Introducing the Care Certificate Evaluation: Innovative practice. (February 2020) - Argyle, Elaine; Thomson, Louise; Arthur, Antony; Maben, Jill; Schneider, Justine; Wharrad, Heather
Although investment in staff development is a prerequisite for high-quality and innovative care, the training needs of front line care staff involved in direct care have often been neglected, particularly within dementia care provision. The Care Certificate, which was fully launched in England in April 2015, has aimed to redress this neglect by providing a consistent and transferable approach to the training of the front line health and social care workforce. This article describes the early stages of an 18-month evaluation of the Care Certificate and its implementation funded by the Department of Health Policy Research Programme.